2017
DOI: 10.15345/iojes.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

How Gifted Students Reach Decisions in Socio-Scientific Issues? Warrants, Information Sources and Role of Media

Abstract: In this research, it was aimed to investigate the decisions of gifted students regarding particular socio-scientific issues with their warrants and information sources on those decisions. The research was qualitative in nature and the participants were 36 (21 male, 15 female) elementary school students who had training at Sinop Science and Art Centre. The data source of the research was a written from consisted nine open ended questions regarding four socio-scientific issues and the data obtained were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…School can be an important source of SSI-related information (Çapkinoglu & Yilmaz, 2018;Connell et al, 2014;Littledyke, 2004;Öztürk et al, 2017). However, some studies concluded that students made little use of school knowledge during reasoning about SSI (Byrne et al, 2014;Covitt et al, 2009;Lundström et al, 2012).…”
Section: Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…School can be an important source of SSI-related information (Çapkinoglu & Yilmaz, 2018;Connell et al, 2014;Littledyke, 2004;Öztürk et al, 2017). However, some studies concluded that students made little use of school knowledge during reasoning about SSI (Byrne et al, 2014;Covitt et al, 2009;Lundström et al, 2012).…”
Section: Knowledgementioning
confidence: 99%
“…These external resources are also recognizable as important within the literature about SSIrelated learning and decision-making. During decision-making about SSI, students' family and friends appear to be an important source of information (Covitt et al, 2009;Lundström et al, 2012;Öztürk et al, 2017;Walsh & Tsurusaki, 2018). Students discuss SSI with family and friends, family and friends stimulate the use of particular media sources, and family practices provide students with information about SSI.…”
Section: External Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have concluded that students made little use of school knowledge during reasoning about SSI (Byrne et al, 2014; Covitt et al, 2009; Lundström et al, 2012), school can nevertheless be an important source of SSI‐related information (Çapkinoglu & Yilmaz, 2018; Connell et al, 2014; Littledyke, 2004; Öztürk et al, 2017). In a large‐scale study among 5688 Australian students aged 16 or 17, students' environmental information sources were questioned (Connell et al, 2014).…”
Section: Sources Of Knowledge About Ssimentioning
confidence: 99%
“…Therefore, it is necessary to find out the thoughts of individuals in different teaching levels about climate change and global warming constituting one of the most significant problems of today's world and to take the necessary steps to determine and eliminate their misconceptions, if they have any. One of these institutions is the Science and Art centers (BILSEM) where gifted children are educated by flexible programs (Öztürk, Eş, & Turgut, 2017).…”
Section: Introductionmentioning
confidence: 99%